Benchmarking Innovation: Comparison of Industrial SMEs in Argentine and France - Rey J, RodrÃguez; D, Galvez; L, Morel; M, Camargo; V, Boly; R, Forradellas (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Benchmarking has become a useful tool for companies for decision-making and improvement of internal practices. Nevertheless, in innovation capabilities, benchmarking applications have been scarce. This study’smain objective was to perform a comparative analysis of the innovation potential of two groups of companies belonging to Argentine and France. Besides the potential for innovation, components of this potential were compared finding strengths and weaknesses of both groups. To do that, the methodology of Innovation Potential Index (IPI) has been used. Through a survey based on acceptance grids, collection of the particularities of both groups has been made. By means of statistical analysis the main differences and similarities have been clarified. Among the most important findings are the similarities between the groups in the classification: in both samples, 60% of cases had a low potential for innovation (passive and reactive categories). Significant differences were found in terms of innovation strategy where French companies performed better than the argentine ones. About innovation project management, Argentinian firms perform better. Human resource results barely developed in the entire sample. The similarities, due to the fact of belong to SME category, results clearly evident. Also differences in some characteristics closely related to markedly different macroeconomic environment have emerged.